Novel cyclohexyl‐based aminophosphine ligands and use of their Ru(II) complexes in transfer hydrogenation of ketones. (15th January 2014) - Kayan, Cezmi; Meriç, Nermin; Aydemir, Murat; Ocak, Yusuf Selim; Baysal, Ak𝚤n; Temel, Hamdi
<x xml:space="preserve">Abstract</x> Two new aminophosphines – furfuryl‐(N‐dicyclohexylphosphino)amine, [Cy2PNHCH2–C4H3O] (1) and thiophene‐(N‐dicyclohexylphosphino)amine, [Cy2PNHCH2–C4H3S] (2) – were prepared by the reaction of chlorodicyclohexylphosphine with furfurylamine and thiophene‐2‐methylamine. Reaction of the aminophosphines with [Ru(η6‐p‐cymene)(μ‐Cl)Cl]2 or [Ru(η6‐benzene)(μ‐Cl)Cl]2 gave corresponding complexes [Ru(Cy2PNHCH2–C4H3O)(η6‐p‐cymene)Cl2] (1a), [Ru(Cy2PNHCH2–C4H3O)(η6‐benzene)Cl2] (1b), [Ru(Cy2PNHCH2–C4H3S)(η6‐p‐cymene)Cl2] (2a) and [Ru(Cy2PNHCH2–C4H3S)(η6‐benzene)Cl2] (2b), respectively, which are suitable catalyst precursors for the transfer hydrogenation of ketones. In particular, [Ru(Cy2PNHCH2–C4H3S)(η6‐benzene)Cl2] acts as a good catalyst, giving the corresponding alcohols in 98–99% yield in 30 min at 82 °C (up to time of flight ≤ 588 h−1). Copyright © 2014 John Wiley & Sons, Ltd.